STUDY OF THERMAL AND ACID STABILITY OF BENTONITE CLAY - Karna Wijaya; Ani Setyo Pratiwi; Sri Sudiono; Emi Nurahmi (Universitas Gadjah Mada, 2002)
The thermal and acid stability of the bentonite clays (Na- and Ca-bentonite) have been tested. The thermal stability testing has been carried out by heating 5 gram of the clays for five hours at 200, 300 and 500 °C respectively, meanwhile acid stability testing was performed by immersing 5 gram clays into 100 mL sulphuric acid 1M, 2M and 3M for 24 hours. The tested clays, then were characterized by means of X-Ray difractometry and IR-spectroscopy methods. The characterization results showed that upon heating, both Ca- and Na-bentonites indicated same thermal stability. However, upon acid treatment, Na-bentonite was found relatively stabiler and more resistance then Ca-bentonite.